MEKANISME PENGANGKATAN ANAK MELALUI PENETAPAN PENGADILAN NEGERI DAN PENGADILAN AGAMA - Dolot A. Bakung (Universitas Negeri Gorontalo, 2010)
Children are a mandate of God that must be conlinuously maintained. whatever its status, the childś inherent dignity of self, and human rights that must be upheld. In practice many questioned the legal basis of making the deed of appointment of the child,Islamic law, adoption agencies do not know which entitles inherit. Even for areas that are still strong influence of Islamic luw also does not recognize adoption agencies. Since enacted, the act number 3 of 2006, Religious Court has been given the authority to request the appointment of handling cases of children based on Islamic law. This is a stabilization of sociological law which has been strengthened among the Indonesian Muslim community. In principle, stipulating the appointment of children through the courts is very different from the determination of the Religious Court primarily concerns the legal consequences arising. Example, in the case of inheriting, the status offoster parents, guardians and others. Keywords: removal of the child, Determination, Religious Courts, Civil court.